2016
DOI: 10.1080/15592324.2016.1139277
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Arabidopsis MAPKKK18 by ABI1 and SnRK2, components of the ABA signaling pathway

Abstract: The plant hormone abscisic acid (ABA), a key regulator in many crucial developmental and physiological processes, recruits diverse components into precisely regulated signaling network. We recently discovered that MAPKKK18, an ABA-activated kinase, is regulated by the protein phosphatase type 2C (PP2C) ABI1 and the kinase SnRK2.6, both components of the ABA core signaling pathway. ABI1 acts to inhibit MAPKKK18 kinase activity, but also affects MAPKKK18 protein turnover via the ubiquitin-proteasome pathway. SnR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…At a transcriptional level, the M3K18 promoter demonstrated higher promoter efficiency following stimulation with ABA in plant guard cells. These results indicated that, MAP3K18 interacts directly with key components of the ABA signaling module, such as SnRK2.6 kinase [19] and PP2C phosphatase ABI1 [17]. ABA engages PYR/PYL ( Figure 1) and prevents the degradation of MAP3K18, which ensures the stability and activation of downstream kinase processes to trigger stress signaling modules [17].…”
Section: Mitogen Activated Protein Kinase (Mapk) Signaling Pathwaymentioning
confidence: 93%
“…At a transcriptional level, the M3K18 promoter demonstrated higher promoter efficiency following stimulation with ABA in plant guard cells. These results indicated that, MAP3K18 interacts directly with key components of the ABA signaling module, such as SnRK2.6 kinase [19] and PP2C phosphatase ABI1 [17]. ABA engages PYR/PYL ( Figure 1) and prevents the degradation of MAP3K18, which ensures the stability and activation of downstream kinase processes to trigger stress signaling modules [17].…”
Section: Mitogen Activated Protein Kinase (Mapk) Signaling Pathwaymentioning
confidence: 93%
“…Consistent with this, studies of the transcriptional regulation of the MKKK18 promotor revealed high promoter activity following ABA stimulation in guard cells ( Mitula et al, 2015 ). Importantly, experimental results indicate that MAPKKK18 interacts directly with two of the key proteins of the ABA core signaling module, PP2C phosphatase ABI1 ( Mitula et al, 2015 ) and kinase SnRK2.6 ( Tajdel et al, 2016 ). ABI1, in the absence of ABA, not only inhibits MAPKKK18 kinase activity by dephosphorylation, but also targets MAPKKK18 for degradation by the ubiquitin-proteasome pathway (UPS) ( Ludwików, 2015 ; Mitula et al, 2015 ).…”
Section: Mapk Cascades In Abscisic Acid Signalingmentioning
confidence: 99%
“…The ABA signaling pathway plays an essential role in regulating plant growth and tolerance to stressful conditions like drought. The coreceptor ABI1 is not only a part of a negative feedback loop within the ABA signaling pathway, but also acts as a hub for hormone cross-talk and is subject to multilevel regulation (17,19,38,39). Our results demonstrate that the ubiquitination of ABI1, mediated by the UBC27-AIRP3 ubiquitination complex, is crucial for ABA responses.…”
Section: Discussionmentioning
confidence: 73%